2020
DOI: 10.1016/j.eclinm.2020.100431
|View full text |Cite
|
Sign up to set email alerts
|

Does the lymph node yield affect survival in patients with esophageal cancer receiving neoadjuvant therapy plus esophagectomy? A systematic review and updated meta-analysis

Abstract: Background Conflicting data have been reported on the prognostic impact of the extent of lymphadenectomy during esophagectomy for esophageal cancer (EC) after neoadjuvant therapy, especially after neoadjuvant chemoradiotherapy (nCRT). Methods A comprehensive online search was performed to explore the association between increased lymph node yield (LNY) and survival of patients with EC, in which the overall survival (OS) was set as the primary outcome. In addition to ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“… 17 The increase in minimum lymph node harvest required to achieve textbook outcome is in line with the increasing evidence that an extensive lymphadenectomy is associated with improved survival and optimized pathological staging, also after neo-adjuvant therapy, as shown in multiple recently published studies. 18–20 The median length of hospital stay decreased with the introduction of enhanced recovery programs and was 9 days for patients after an uncomplicated esophagectomy in the Netherlands, probably contributing to the decreased maximum hospital days to achieve textbook outcome. 21 , 22 Although these changes to the original textbook outcome seem to follow recent findings regarding esophageal cancer treatment in literature, no actual rationale for the inclusion of each of the items was provided by the responding surgeons.…”
Section: Discussionmentioning
confidence: 96%
“… 17 The increase in minimum lymph node harvest required to achieve textbook outcome is in line with the increasing evidence that an extensive lymphadenectomy is associated with improved survival and optimized pathological staging, also after neo-adjuvant therapy, as shown in multiple recently published studies. 18–20 The median length of hospital stay decreased with the introduction of enhanced recovery programs and was 9 days for patients after an uncomplicated esophagectomy in the Netherlands, probably contributing to the decreased maximum hospital days to achieve textbook outcome. 21 , 22 Although these changes to the original textbook outcome seem to follow recent findings regarding esophageal cancer treatment in literature, no actual rationale for the inclusion of each of the items was provided by the responding surgeons.…”
Section: Discussionmentioning
confidence: 96%
“…The median number of LN removed at surgery for the entire cohort and the 42 patients who experienced locoregional relapse as the first progression was 21.0 (IQR, 15.0–26.0) and 21.5 (IQR, 16.8–26.0), respectively. Based on the dissected LN number, lymphadenectomy appeared to be adequate in the present study [ 10 , 11 ]. Although CCRT induced regression of cancer cells in the LN, it might cause fibrosis of the nodes, making residual cancer cells adhere to the surrounding tissues, and leading to locoregional relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have confirmed the association between the number of resected lymph nodes and the prognosis of ESCA (8)(9)(10). According to the current clinical guidelines, extensive lymphadenectomy can provide survival benefits and is hence considered the gold standard of treatment (11).…”
Section: Introductionmentioning
confidence: 89%